Innovation and Criminal Justice: Editorial Introduction to the Special Issue on 'Innovation', December 2017 - Graham, Hannah (European journal of probation, 2017)
This Special Issue of the European Journal of Probation considers examples and influences of innovation within criminal justice and community contexts. It offers some timely and insightful contributions from different countries to broader discussions of innovation in this field, a multi-faceted topic which piques significant interest but has perhaps not yet received the level of sustained critical analytical engagement it warrants. This editorial introduction critically reflects on a series of questions and problematisations of innovation and criminal justice. Questions about the forms and functions (‘what’, ‘where’ and ‘how’) of innovation in criminal justice should not be divorced from questions about its architects and beneficiaries, including their intentions and ideologies (‘who’ and ‘why’). Following this, a brief overview of the Special Issue is provided. There is much more yet to be done, as well as celebrated in this area